Prototipe Sistem Monitoring Parameter Air Akuarium Ikan Dengan Konsep IoT Menggunakan Aplikasi Berbasis Android - Deny Setiawan; Sartika Lina Mulani Sitio (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Monitoring the parameters of temperature and pH of the water in fish aquariums is one of the things that is needed to determine the quality of the water in the aquarium. This can ensure that the condition of the fish kept is maintained in good health. Currently monitoring the quality of water temperature and pH is still done manually. This causes the hobbyist to always be near the aquarium by holding a manual tool to determine the quality of the temperature and pH of the water. In order to monitor the quality of aquarium water efficiently and effectively by the hobbyist, an aquarium water quality monitoring system is needed that can inform the hobbyist automatically and in real time. In realizing this, it can take advantage of technological developments using the concept of the Internet of Things (IoT). Internet of Things is the concept of sending microcontroller data obtained from connected sensors. The application of the IoT concept is carried out by building a prototype using the DS18B20 temperature sensor and the DFROBOT SEN 0161 pH sensor. The Arduino UNO R3 microcontroller and the ESP8266-01 module are also needed to process sensor data and connect the prototype to the internet via wi-fi so that it can send measurement data to Firebase. Real-time Database. To inform the sensor measurement data to the hobbyist using the Android-based application "Simpel Monitoring". As for the implementation and the results of the tests carried out, the prototype that was built was able to send temperature and pH sensor data to the Firebase Realtime Database and was successfully displayed through the "Simpel Monitoring" application with the help of an internet connection. The percentage of pH sensor accuracy obtained was 99.99% and the percentage of temperature sensor accuracy was 97.3%.